(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article is an imitation of the idea that the backwardness of science and enlightenment is the struggle against ignorance, the path chosen by independent Uzbekistan, that is, "The struggle against ignorance should be fought only with enlightenment."